Influenza SIRS with Minimal Pneumonitis - Erramilli, Shruti; Mannam, Praveen; Manthous, Constantine A. (Frontiers in Medicine, 2016)
Although systemic inflammatory response syndrome (SIRS) is a known complication of severe influenza pneumonia, it has been reported very rarely in patients with minimal parenchymal lung disease. We here report a case of severe SIRS, anasarca, and marked vascular phenomena with minimal or no pneumonitis. This case highlights that viruses, including influenza, may cause vascular dysregulation causing SIRS, even without substantial visceral organ involvement.